National security of Ukraine in the modern world: Problems of strategic communications development in the context of European integration - Shchepanskiy, Eduard; Grytsyshen, Dymytrii; Maievskyi, Yurii; Marushchyn, Yurii; Savitskyi, Vladyslav (Edelweiss Applied Science and Technology, 2024)
The article attempts to conduct theoretical analysis of today security paradigms based on the case of national security of Ukraine in the context of current Russo-Ukrainian war and its surrounding landscape of interests and discourses. Interests of various players and stakeholders, as well as corresponding prospects are analyzed. The findings allowed raising the problematic of alternative peacemaking and peacebuilding – through strategic communications and geoeconomics discourse.